2009
DOI: 10.1111/j.1743-7563.2009.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of S‐1 and irinotecan combination chemotherapy as a first‐line therapy for patients with advanced gastric cancer. Korean Cancer Study Group Protocol ST05‐02

Abstract: Background: Irinotecan plus intravenous 5-fluorouracil (5-FU) with leucovorin is effective against gastrointestinal cancer. S-1 is an oral fluoropyrimidine derivative and has a high response rate of about 40% for patients with advanced gastric cancer (AGC). We evaluated the antitumor activity and toxicities of an S-1 and irinotecan combination as a first-line therapy for patients with AGC. Methods: Patients with histologically confirmed unresectable or metastatic AGC were treated with S-1 40 mg/m 2 PO twice da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In addition, many patients have primary refractory disease (Catalano et al 2008). Therefore, development of novel molecularly targeted therapeutics is required to improve the treatment outcome for gastric cancer patients (Weichert et al 2008;Kang et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, many patients have primary refractory disease (Catalano et al 2008). Therefore, development of novel molecularly targeted therapeutics is required to improve the treatment outcome for gastric cancer patients (Weichert et al 2008;Kang et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Recent randomized trials yielded encouraging results for S-1-containing doublets. [5][6][7] Docetaxel showed synergism with S-1 in vitro, and the response rate was 46%-67% in several phase 2 trials. [9][10][11] Based on these findings, we designed a randomized phase 2 study to determine whether S-1 or cisplatin shows greater promise as a combination partner of docetaxel for a subsequent phase 3 study.…”
mentioning
confidence: 99%
“…Uedo et al tried 80 mg/m 2 (40 mg/m 2 /week) and reported ORR of 48%, while Komatsu et al, derived from phase I study by themselves, adopted 125 mg/m 2 (62.5 mg/m 2 /week) to obtain better ORR of 54% [ 20 , 21 ]. A Korean study favored triweekly schedule with 150 mg/m 2 (50 mg/m 2 /week) irinotecan with ORR of 49% [ 22 ]. Despite some various ranges of S-1 dose among the studies, we thought that these findings mainly implied dose–response relationship of irinotecan might exist.…”
Section: Discussionmentioning
confidence: 99%